Current childhood cancer survivor long-term follow-up practices in South Africa - Zyl, Anel van; C Rogers, Paul; Kruger, Mariana (Journal of Advanced Pediatrics and Child Health, 2020)
Background: The number of childhood cancer survivors (CCSs) is increasing due to improved survival. Most suffer at least one treatment-related late effect, even decades after treatment, thus lifelong long-term follow-up (LTFU) care is a necessity. Currently no standardized LTFU programme for CCSs exists in South Africa. Study purpose: This study investigated current LTFU care of CCSs in South Africa. Methods: A survey was conducted amongst 31 South African paediatric oncologists using the SurveyMonkeyTM online tool. Information obtained included: training/experience, LTFU practices, late effects knowledge and opinion regarding the importance of a standardized LTFU programme. Results: The response rate was 74% (23/31). Respondents had an average of 9 years’ experience. All (22/23; 96%) regarded LTFU as important. Only half (12/23; 52%) discussed late effects at diagnosis. Infertility and second malignancy risks were discussed by a third. Less than half (48%) used LTFU guidelines; the majority (9/11; 82%) adjusted them to the local context. Most survivors were followed by a paediatric oncologist (17/23; 74%). About half of respondents (47.8%) shared LTFU with colleagues in private practice (50%), secondary (66.7%) or primary care facilities (25%). Almost half of respondents (10/23; 43.5%) regarded their late effects knowledge and LTFU experience as good, 8/23 (34.8%) as adequate and 3/23 (13%) as inadequate. All agreed that a national LTFU programme would be very important (87%) or important (13%). Almost half of the respondents (48%) understood what a Survivorship Passport was. Conclusion: It is essential to develop a national standardized LTFU programme for CCSs in South Africa to ensure appropriate care for all survivors.